Massive digestive hemorrhage from secondary fistulas of great vessels to the digestive tract - Chacaltana Mendoza, Alfonso (2020)
The formation of a fistula between large caliber arteries and the digestive tract is an uncommon complication of reconstructive surgery of the large vessels secondary to the use of vascular prostheses, which manifest themselves with massive hemorrhages with high mortality. We report two cases of aorto-enteric fistula and carotid-esophageal fistula that share common characteristics such as the clinical manifestation of massive and fatal gastrointestinal bleeding in patients with a history of vascular prosthesis placement.